A Public Strategy for Compliance Monitoring - Gauri, Varun; Staton, Jeffrey K.; Vargas Cullell, Jorge (World Bank, Washington, DC, 2013)
Theoretical accounts of compliance with court orders emphasize the importance of transparency. Most empirical studies of compliance center on high profile political cases, largely ignoring the high-volume, quotidian claims against the state for basic services that constitute the largest share of court dockets in many jurisdictions. This paper uses a unique dataset on compliance with orders from the Constitutional Chamber of the Supreme Court of Costa Rica to examine the determinants of compliance in low salience cases. It finds that orders issued just after the Court announced, in a press conference, that it was monitoring compliance were implemented roughly two months sooner than orders issued just prior to the press conference. These findings suggest that publicity can motivate compliance even in low salience cases.